2022
DOI: 10.3928/00989134-20220606-04
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Nurse-Led Mobility Protocols for Hospitalized Older Adults: A Systematic Review

Abstract: Hospitalized older adults (aged ≥65 years) are at risk for functional decline and negative outcomes associated with immobility, such as pressure injuries and falls. There is a paucity of research that examines impacts of mobility interventions in older adults in medical surgical units. The current systematic review examines the impact of mobility-related interventions in this population. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses guided this review. Eligibility determination and dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…In this study, we observed that hospitalized patients spend a significant proportion of their days at low or middle levels of mobility 26,27 . Current recommendations on fall prevention advocate that the clinical team prioritize promoting safe patient mobility to help avoid complications from prolonged immobility and bed rest 28,29 . We observed a trend that nonfallers spent more time at JH-HLM levels of 7 or 8 representing longer ambulation distances, but we may not have been powered to see the impact of this.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In this study, we observed that hospitalized patients spend a significant proportion of their days at low or middle levels of mobility 26,27 . Current recommendations on fall prevention advocate that the clinical team prioritize promoting safe patient mobility to help avoid complications from prolonged immobility and bed rest 28,29 . We observed a trend that nonfallers spent more time at JH-HLM levels of 7 or 8 representing longer ambulation distances, but we may not have been powered to see the impact of this.…”
Section: Discussionmentioning
confidence: 77%
“…26,27 Current recommendations on fall prevention advocate that the clinical team prioritize promoting safe patient mobility to help avoid complications from prolonged immobility and bed rest. 28,29 We observed a trend that nonfallers spent more time at JH-HLM levels of 7 or 8 representing longer ambulation distances, but we may not have been powered to see the impact of this. Injurious falls are not frequent hospital events, so larger studies are needed to examine the role of keeping patients more mobile to help reduce injurious falls.…”
Section: Discussionmentioning
confidence: 93%
“…Without adequate pain control, patients either do not want to or cannot mobilize and participate in rehabilitation therapy. 31 With the aging US population, it is imperative to find ways to better treat these patients so they can return to their acceptable quality of life. Doing so will improve outcomes not only for patients but also for the health care system with reduced costs and overutilization.…”
Section: Discussionmentioning
confidence: 99%
“…Regular physical activity during hospitalization is vital to help patients regain their functional abilities. Without adequate pain control, patients either do not want to or cannot mobilize and participate in rehabilitation therapy 31…”
Section: Discussionmentioning
confidence: 99%